PERBANDINGAN EFEKTIFITAS HASIL PENGGELONTORAN SEDIMEN DI WADUK CARA FLUSHING DAN SLUICING - Pranoto S. Atmodjo; Sri Sangkawati; Kirno Kirno (TEKNIK, 2013)
This study compares the effectiveness of the flushing of sediment in the reservoir by means of flushing andSluicing way, based on Physical Hydraulic Test (Model Test) in the laboratory. Flushing is removingaccumulated deposited sediment. While slucing is releasing of sediment through the reservoir beforesettled or keep sediment remain in suspension and its occur during flood period. Sediments FlushEffectiveness represented by the percentage of released sediment by sediment deposited or the amount ofsediment entering the reservoir during the flushing period.The model based on the prototipe from DetailDesign of Structural Countermeasures for Sedimentation on Wonogiri Reservoir by Nippon Koei 2009.Running model duration is one hour, used free flow and submergence condition, with discharge variationQ=100, 200 and 400 m3/s. Sluicing experiments conducted with some 60 liters of sediment sprinkle evenlywide flow, and Flushing implemented by 2,00 m thickness of deposited sediment that spreaded over thereservoir bottom before running. From this research showed that Sluicing way more efficient than theflushing way, where the number of efficiency of sediment Sluicing way bigger than the efficiency offlusing way, in the running an hour in the laboratory test